Mdm2 protein expression is strongly associated with survival in malignant pleural mesothelioma. (June 2014) - Mairinger, Fabian D; Walter, Robert FH; Ting, Saskia; Vollbrecht, Claudia; Kollmeier, Jens; Griff, Sergei; Hager, Thomas; Mairinger, Thomas; Christoph, Daniel C; Theegarten, Dirk; Schmid, Kurt Werner; Wohlschlaeger, Jeremias
ABSTRACT: : Aims: TP53 mutations are extremely rare in malignant pleural mesothelioma (MPM). In TP53 wild-type tumors, the functional p53 protein can be inactivated by MDM2 .Materials & methods: A total of 61 patient samples were tested for their Mdm2 and p53 protein expression levels via immunohistochemistry.Results: This study demonstrates nuclear Mdm2 expression in three out of four mesothelioma cell lines and 21.3% of the MPM specimens investigated. After silencing of the MDM2 gene by siRNA in MPM cell lines, Mdm2 immunoexpression is lost and cells show changes indicative of severe damage. Mdm2 protein expression in MPM is detected in epithelioid and biphasic subtypes only and is significantly associated with poor survival compared with Mdm2-negative tumors. This may be explained by increased Mdm2 levels possibly leading to an increased ubiquitilation and proteasomal degradation of functional p53 protein.Conclusion: Expression of Mdm2 is a strong prognostic factor associated with shortened overall survival in MPM.